Evaluation of Gum Arabic Double-layer Microneedle Patch Containing Sumatriptan for Loading and Transdermal Delivery - Zhang, Xiaoduo; Liu, Weijun; Wang, Wei; Pi, Mingli; Huang, Beibei; Wu, Fanhong (Current Drug Delivery, 2024)
Background: As episodes of acute migraine for migraineurs, a self-treatment that promptly relieves headaches and eliminates the associated symptoms would be optimal. Based on the consideration, a rapidly dissolving double-layer microneedles derived from natural acacia was developed. Methods: Under the optimized reaction conditions that was screened out through orthogonal designing test, acacia (GA) was conducted on the ionic crosslinking, a prescribed amount of cross-linking composites was applied to fabricate the double-layer microneedles loaded with sumatriptan at the tip. The mechanical strength and dissolving capability of penetrating pigskin along with in vitro release were measured. The component and content of the resulting compound were determined with FT-IR and thermal analysis, and the bonding state of cross-linker was characterized using X-ray photoelectron spectroscopy. Results: Each needle from the constructed microneedles with the maximal drug loading consisted of the crosslinking acacia of around 10.89 μg and the encapsulated sumatriptan of around 1.821 μg. Apart from the excellent solubility, the formed microneedles possessed enough mechanical stiffness to penetrate the multilayer parafilm. The histological section of the pigskin confirmed the insertion depth of the microneedles could reach 300 ± 28 μm, and the needle bulk in the isolated pigskin could be totally dissolved within 240 s. Franz diffusion study displayed that an almost entire release of the encapsulated drug might be realized within 40 min. The coagulum created from crosslinking was composed of -COOof glucuronic acid in the component of acacia and the added crosslinker to form a double coordination bond, and the crosslinking percentage reached about 13%. Conclusion: The release amount of drug from 12 patches made of the prepared microneedles was comparable to that of subcutaneous injection, providing a new possibility for migraine treatment.
Keywords: migraine